The transnational dissemination and reception of Portuguese poetry: Espanca, Andresen and Amaral - Pazos Alonso, C (Edinburgh University Press, 2023)
As the country of two giants of the western literary canon, the renaissance Luís de Camões and the modernist Fernando Pessoa, Portugal has long been inclined to see itself as a land of poets, an image it sought to promote abroad too. Both male bards were tasked with embodying and signifying the essence of Portuguese culture.1 But it begs the question: where are their female counterparts? Insofar as women have been less likely to be called upon to represent the nation, how much of a disadvantage is their marginalization when it comes to translation? To investigate how female artists fare in their journey into the Anglosphere, this article centres on three case studies, all widely regarded as major poets in the Portuguese-speaking world and beyond: Florbela Espanca (1894–1930), Sophia de Mello Breyner Andresen (1919–2004), and Ana Luísa Amaral (1956–2022). Together, they offer an intellectually and artistically varied sample, spanning the last one hundred years.